"I Just Beared Through It": Southern US Christian Women's Experiences of Chronic Dyspareunia. Issue 2 (April 2020) - Happel-Parkins, Alison; Azim, Katharina A.; Moses, Amy
Abstract : Background: Research has shown that up to 53% of adult women, at some point in their lives, suffer from pelvic floor dysfunction in the United States, although it is frequently underdiagnosed. Dyspareunia is a type of pelvic floor dysfunction that is identified as pain with sexual intercourse, tampon insertion, vaginal examinations, vaginal stimulation, and other occurrences involving vaginal touch. There are a limited number of studies that use qualitative approaches investigating women's experiences of dyspareunia. Objectives: The purpose of this qualitative study was to explore the emotional, physical, and psychological experiences of self-identified Christian women from the Midsouthern United States who have been recently diagnosed with dyspareunia associated with pelvic floor muscle overactivity. The research question was: How do self-identified Christian women in the Midsouthern United States experience dyspareunia? Study Design: Narrative inquiry was the qualitative methodology used for this study. Methods: Methods of data collection included questionnaires followed by semistructured interviews with 8 women. Results: Thematic analysis was used to discuss 4 themes: (1) misdiagnosis and dismissal (personal and medical) of chronic dyspareunia; (2) individualized strategies for coping with chronic dyspareunia; (3) sex (mis)education: influences of abstinence-only approaches, purity culture, and peer pressure; and (4) understandings about sex, religion, and pelvic pain. Conclusion: Primary care physicians, gynecologists, and pelvic floor physical therapists are encouraged to recognize the importance of factoring sociocultural aspects, such as religion, into their patient care and treatment, and to proactively discuss them during patient assessment. Pelvic floor physical therapists are encouraged to address women's sociocultural contexts, including potential exposure to religious messages of shame and fear, during patient intake, and possibly throughout treatment.